ANALISIS INVESTASI SAHAM PERUSAHAAN GO PUBLIC SEKTOR PERTANIAN DI BURSA EFEK JAKARTA - Artie Arditha R; Endang Asliana (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
Investors, in a capital market, have to observe and analyze the companies’ stock price movements in order to minimize the risk in having stock investments. One of the techniques in analyzing companies’ performance is the stock investment analysis or portfolio analysis. By using the portfolio analysis, this research finds out the best combination of stock investment of PT PP London Sumatera Tbk. (LSIP) and PT Astra Agro Lestari Tbk. (AALI), as go public agricultural companies listed in Jakarta Stock Exchange. After finding the best combination of stock investment of those companies, this research also finds out whether the combination is at the optimum portfolio which would be on the least risk and a particular return or on the highest return and a particular risk. The research was held in 2006 and the data was taken from January 2004 to December 2005. The data was processed by using statistical software in order to minimize the human error. The result shows that there are two best combinations of stock investment on those companies. Those combinations are at the optimum portfolio. The first combination shows 30% of stock investment in LSIP and 70% stock investment in AALI, while the second combination shows 20% stock investment LSIP and 80% stock investment AALI. Investors should choose one of these combinations, because according to the research, these combinations would give them the best return at the least risk.